Strategi Pemberian Label Nama Pada Produk Susu Kambing Etawa di Desa Tanjungan, Kemlagi Mojokerto Dalam Upaya Meningkatkan Nilai Jual dan Daya Saing - Inuk Wahyuni Istiqomah; Ahmad Firmansyah; Mohamad A’ang Fahrurrozi; Lailil Nashofatul Ummah; Tasya Avrillia Frastya; Cindy Kurnia Permatasari; Juan Dwi Saputra; Satrio Agung Buono; Augusta Detya Rahmanda; Ainun Alfiyah; Andini Apriliya Cahya; Bela Sophia Putri; Muhammad Abid Muridulloh; Sofynda Cahyaningrum; Aldion Dwi Sakti; Riski Wijaya Kusuma; Sindy Fitrianingsih; Yobel Putra Ardana; Faizatul Iza; Al Fauqi Nur Kharisi; Akmad Risfan Sholiqun; Elvira Rahma Trinia (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Tanjungani Village,i Kemlagi,i hasi greati potentiali asi ai produceri ofi qualityi Etawai goati milk.i However,i thei lacki ofi producti identity,i suchi asi namei labels,i hindersi competitivenessi ini thei market.i thisi communityi servicei aimsi toi developi ai strategyi fori providingi namei labelsi oni Etawai goati milki productsi toi increasei thei sellingi valuei andi attractivenessi ofi thei product.i Thei methodsi usedi includei datai collectioni throughi interviewsi andi observations,i labeli designi basedi oni locali characteristics,i andi marketi testingi toi evaluatei itsi effectiveness.i Buildingi consumeri trust,i andi creatingi ai morei professionali producti image.i Ini addition,i labelsi thati includei locali identityi strengtheni thei brandingi ofi thei Tanjungani Villagei area.i thisi communityi servicei concludesi thati providingi namei labelsi isi ani effectivei strategyi toi supporti marketingi andi expandi thei reachi ofi Etawai goati milki products.